Pediatrics Guillain-Barré Syndrome: A case series (Research, Society and Development, 2023)
This research aimed to evaluate clinical and epidemiological features of patients aged 1 to 13 years, diagnosed with Guillain-Barre Syndrome (GBS) in a Universitary Hospital between January 2019 and June 2023. It was performed a retrospective, descriptive analysis of medical records. There were 5 cases recorded with the usual manifestation of GBS, progressive ascending paralysis with diminished reflexes, with varying evolution time. Only two cases had associated diminished sensibility. Four cases had their cerebrospinal fluid analyzed, which was useful in confirming the diagnosis. An electroneuromyography study was performed in the 5 cases, with only one case of the demyelinating form of GBS and the other four cases being the motor axonal form. Through the analysis of clinical history, previous infectious symptoms, serological and viremia tests, it was possible to presume an etiology in two cases, being previous COVID-19 and Gastroenteritis. One case had a temporal correlation with the Poliomyelitis Oral Vaccine and anti-Yellow Fever vaccine. They were all treated with Human Immunoglobulin in order to reduce the recovery time, with a positive effect in three cases. One of the other cases had a cardiorespiratory arrest in the fourth day of Immunoglobulin administration and the other case didn’t show any response with the first dose, so the dose was repeated, when the patient finally presented a positive response. In conclusion, cases of GBS have varying time evolution and level of severity, so it’s necessary to recognise the symptoms and diagnosis fastly, in order to start the treatment, preventing greater disability.